Implementation of TOPSIS Method to Assist the Process of Accepting New Employees in the Company - Astrid Noviana Paradhita; Yeni Fajariyanti; Muhammad Tafdhil Amanda; Agreianti Puspitasari; Vivin Sulistyowati (Research Synergy Foundation, 2025)
Human resources play an important role in ensuring that all business processes in a company run smoothly. Human resources in a company must have competencies and skills that match the company’s needs. The employee recruitment process is the first gateway that must be carried out comprehensively to obtain reliable human resources. However, the company’s recruitment process is still at risk of bias and takes a long time. This study was conducted to identify a strategy for recruiting new employees who are competent according to the qualifications required by the company. This study was developed by applying a preference ordering technique based on similarity to the ideal solution (TOPSIS). The data criteria used in the study were based on a selection process commonly used in one of the state-owned companies in Indonesia, which included the results of a general intelligence test (TIU), a national insight test (TWK), a field ability test (TKB), and an interview test. The weighting used was TIU 30%, TWK 10% TWK, 20% TKB, and 40% for the interview test. The study results showed that the TOPSIS method can help companies find employees with the competencies that best match the qualifications needed. TOPSIS can also increase the efficiency of the recruitment process time by up to 70%. TOPSIS can help companies find the best 20 candidates in just 7 days, whereas, in the recruitment process, without TOPSIS, the company needs 21 to 30 days. Using TOPSIS, companies can streamline the recruitment process, reduce bias, and reduce maintenance costs.